2014
DOI: 10.1080/11250003.2014.953218
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of fire on Papilionoidea (Lepidoptera) communities: a pilot study in Mediterranean maquis shrubland

Abstract: In the Mediterranean landscape fires are common, sometimes arising due to human activity. Fire influences the amount of sunlight that reaches the ground, thus affecting the diversity and distribution of animal and plant species. In this study, we analysed the effect of fire on butterfly diversity at the Site of Community Importance (SCI) "Monti di Lauro" (IT8040013) in southern Italy (Campania). The area covers 7040 ha and is mainly characterised by Mediterranean maquis and woody vegetation. We compared the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In particular, it occurs in the less potentially profitable areas, which are either too steep or on too meagre soils, and is very frequent all along the Italian peninsula, particularly in the Apennines. The occurrence of bushfires (7.1.1) is widespread in the Mediterranean area, and may be detrimental to narrowly endemic species (Scandurra et al ., ), such as Pseudophilotes barbagiae (DD), or Spialia therapne (NT) but may occasionally threaten also some species flying at higher elevations, such as Polyommatus galloi (VU). Under the general IUCN threat category of ‘ecosystem modification’ also falls the excessive pumping from the water table, which is becoming increasingly widespread mostly during summer, for both agricultural and household needs.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it occurs in the less potentially profitable areas, which are either too steep or on too meagre soils, and is very frequent all along the Italian peninsula, particularly in the Apennines. The occurrence of bushfires (7.1.1) is widespread in the Mediterranean area, and may be detrimental to narrowly endemic species (Scandurra et al ., ), such as Pseudophilotes barbagiae (DD), or Spialia therapne (NT) but may occasionally threaten also some species flying at higher elevations, such as Polyommatus galloi (VU). Under the general IUCN threat category of ‘ecosystem modification’ also falls the excessive pumping from the water table, which is becoming increasingly widespread mostly during summer, for both agricultural and household needs.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between wildfires and insects has been studied in many taxa (Lepidoptera, Coleoptera and Orthoptera) (Chambers & Samways, 1998; De Andrade et al, 2014; Elia et al, 2012; Scandurra et al, 2014; Thom et al, 2015; Thompson et al, 2022; Ulyshen et al, 2020). Warren et al (1987) and Moreno and Oechel (2012) reported that grasshoppers with a good flight capability are less sensitive to fires, as they can better escape fires than nymphs or flightless species.…”
Section: Discussionmentioning
confidence: 99%